Occupational Accidents among Fishermen in Manado, North Sulawesi - Fitri M. Suhartoyo; Oksfriani J. Sumampouw; Novie H. Rampengan (Universitas Sam Ratulangi, 2022)
Abstract: The International Labor Organization (ILO) noted that at global level more than 2.78 million people die per year due to occupational accidents or work-related diseases. In addition, there are approximately 374 million injuries and illnesses resulting from non-fatal occupational accidents each year. The Food and Agriculture Organization (FAO) in